LIPUS as a potential strategy for periodontitis treatment: A review of the mechanisms - Aimaijiang, Maierhaba; Liu, Yiping; Zhang, Zhiying; Qin, Qiuyue; Liu, Manxuan; Abulikemu, Palizi; Liu, Lijun; Zhou, Yanmin (Frontiers in Bioengineering and Biotechnology, 2023)
Periodontitis is a chronic inflammatory condition triggered by oral bacteria. A sustained inflammatory state in periodontitis could eventually destroy the alveolar bone. The key objective of periodontal therapy is to terminate the inflammatory process and reconstruct the periodontal tissues. Conventional treatments (e.g., flap debridement) aim to control the infection, but they fail to restore the periodontal supporting structures. Low-intensity pulsed ultrasound (LIPUS), as acoustic energy, transmits the mechanical signals to the target tissue to provide non-invasive physical stimulation. LIPUS has positive clinical effects, including the promotion of bone regeneration, soft-tissue regeneration, inflammation inhibition, and neuromodulation. LIPUS can maintain and regenerate alveolar bone during an inflammatory state by suppressing the expression of inflammatory factors. LIPUS also affects the cellular behavior of periodontal ligament cells (PDLCs), thereby protecting the regenerative potential of bone tissue in an inflammatory state. However, the underlying mechanisms of the LIPUS therapy are still yet to be systematically summarized. The goal of this review is to outline the potential cellular and molecular mechanisms of periodontitis-related LIPUS therapy, as well as to explain how LIPUS manages to transmit mechanical stimulation into the signaling pathway to achieve inflammatory control and alveolar bone regeneration.